The 1730 Great Metropolitan Chile Earthquake and Tsunami Commemoration: Joint Efforts to Increase the Country’s Awareness - Natalia Zamora; Alejandra Gubler; Víctor Orellana; Jorge León; Alejandro Urrutia; Matías Carvajal; Marco Cisternas; Patricio Catalán; Patricio Winckler; Rodrigo Cienfuegos; Cristóbal Karich; Stefan Vogel; et al. (Geosciences, 2020)
On 8 July 1730, a great earthquake struck metropolitan Chile, causing extensive damage 1000 km along the country and focused in Valparaíso. Due to the date of occurrence of this event, large uncertainties about the earthquake’s magnitude have been discussed among the scientific community, and the earthquake and tsunami have remained unknown for most of the population. The purpose of this paper is to describe joint efforts undertaken by organizations, academia, and authorities to rescue the forgotten memory of an event that occurred almost three centuries ago and that may be repeated in the near future. In line with the Sendai Framework, we focus on one of the four priorities for action, which is to understand disaster risk, with the premise that the memory activation and raising awareness can save lives in the future. We designed outreach strategies to communicate this knowledge to the community in a participatory way. The latter involves scientific talks, earthquake simulators, tsunami projection mapping on relief scaled models (mock-up), and a public debate including the participation of academia, politicians, authorities, and the local community. The emulation of such activities and the constant work of regional and national authorities, academia, and non-governmental organizations dealing with risk mitigation encourage involving the community to build safer cities against the tsunami hazard.